Labor Market Careers before and after Incarceration - Bence Czafit; János Köllő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
We study the entry to formal employment and earnings of a large sample of convicts released from Hungarian prisons in 2002-2008. We identify the effect of the prison service on post-release careers by exploiting differences in the timing of incarceration, on the one hand, and estimating fixed effects models, on the other. For convicts with a single prison spell,we find initially negative effect on employment that turns positive after about one year while the impact on wages is permanently negative. A comparison with recidivists, for whom the employment effect is negative and the wage effect is weaker, suggests that these results are driven by a drop in the reservation wages of converted criminals rather than the lack of discrimination. This reading is supported by further data showing that the ex-inmates, on average, make increased effort to find legitimate sources of living and support to finding jobs.
Keywords: K42; J64; J39; 330; incarceration; unemployment; wage loss; discrimination